2018
DOI: 10.1371/journal.pone.0195995
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of a sensitive and independent stabilometry parameter set

Abstract: Recent studies have suggested reduced independent and sensitive parameter sets for stabilometry measurements based on correlation and variance analyses. However, the reliability of these recommended parameter sets has not been studied in the literature or not in every stance type used in stabilometry assessments, for example, single leg stances. The goal of this study is to evaluate the test-retest reliability of different time-based and frequency-based parameters that are calculated from the center of pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
(57 reference statements)
5
33
0
1
Order By: Relevance
“…In this study, COP parameters, including the sway area (mm 2 ), path length (cm), and speed (cm/s) of COP displacement, were measured as primary outcomes ( Figure 2 A). COP parameters were reliable for 30 s in a bipedal position [ 25 , 26 ]. Therefore, the sampling duration of COP measurements was set to 60 s, as suggested by Carpenter et al [ 27 ], and was measured from 60 s after performing the SEM.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, COP parameters, including the sway area (mm 2 ), path length (cm), and speed (cm/s) of COP displacement, were measured as primary outcomes ( Figure 2 A). COP parameters were reliable for 30 s in a bipedal position [ 25 , 26 ]. Therefore, the sampling duration of COP measurements was set to 60 s, as suggested by Carpenter et al [ 27 ], and was measured from 60 s after performing the SEM.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, postural sway is often analysed using a force distribution measuring plate, which provides the two-dimensional wandering of the CoP in the AP and the ML directions [13,[33][34][35], which is then used to define stabilometry parameters [36][37][38]. In case of a uniaxial balance board, oscillations in ML direction are negligible compared to the those in the AP direction, consequently, the balancing task can be described as a one-dimensional motion.…”
Section: Stabilometry Parametersmentioning
confidence: 99%
“…Nagymáté et al [36,37] and Petró et al [38] collect the most often used stabilometry parameters that can be found in the literature for the characterization of human balancing ability in the AP and the ML directions. Here, we adopt these concepts to the changes in the angles φ a , φ h and φ b .…”
Section: Stabilometry Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different parameters can be found in the literature to characterize the performance during balancing tasks, such as mean power frequency, median frequency, frequency range power ratios, spectral power AP-ML ratio, largest amplitude and corresponding largest frequency, just to mention a few [29,30]. In a previous work of the authors [23], the standard deviation of the balance board angle was used as a measure of balancing skill.…”
Section: Stabilometrymentioning
confidence: 99%